2021
DOI: 10.3389/fbioe.2021.766399
|View full text |Cite
|
Sign up to set email alerts
|

TEMPO-Oxidized Cellulose Nanofiber-Alginate Hydrogel as a Bioink for Human Meniscus Tissue Engineering

Abstract: Objective: The avascular inner regions of the knee menisci cannot self-heal. As a prospective treatment, functional replacements can be generated by cell-based 3D bioprinting with an appropriate cell source and biomaterial. To that end, human meniscus fibrochondrocytes (hMFC) from surgical castoffs of partial meniscectomies as well as cellulose nanofiber-alginate based hydrogels have emerged as a promising cell source and biomaterial combination. The objectives of the study were to first find the optimal formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
(83 reference statements)
1
20
0
Order By: Relevance
“…Frontiers in Bioengineering and Biotechnology frontiersin.org The TCNF/ALG constructs showed more of an inner meniscus-like phenotype while the collagen I-based construct was consistent with a more outer meniscus-like phenotype Lan et al (2021) (Continued on following page)…”
Section: Figurementioning
confidence: 98%
See 2 more Smart Citations
“…Frontiers in Bioengineering and Biotechnology frontiersin.org The TCNF/ALG constructs showed more of an inner meniscus-like phenotype while the collagen I-based construct was consistent with a more outer meniscus-like phenotype Lan et al (2021) (Continued on following page)…”
Section: Figurementioning
confidence: 98%
“…Lan et al fabricated TEMPO (2,2,6,6tetramethylpiperidine-1-oxyl)-oxidized cellulose nanofiber/ alginate (TCNF/ALG) hydrogel and suggested that human meniscus fibrochondrocytes (hMFC) implanted in the hydrogel exhibited a more inner meniscus-like phenotype, whereas cells cultured in a collagen I-based construct exhibited a more outer meniscus-like phenotype (Lan et al, 2021). As another common hydrogel ingredient, agarose is widely used to prepare gels for separating macromolecular A 3D printing wedge-shaped poly (ε-caprolactone) (PCL) scaffold as a backbone, in vitro cell study and scaffolds were implanted in the meniscus defect and sutured to the residual rim after the mature New Zealand White rabbits underwent total medial meniscectomy except 5% of the external rim in vivo 2% of meniscus extracellular matrix (MECM)-based hydrogel strongly enhanced chondrogenic marker mRNA expression and cell proliferation; PCL-hydrogel-MFCs group exhibited markedly better gross appearance and cartilage protection than other groups and the regenerated menisci in the PCL-hydrogel-MFCs group had similar histological structures, biochemical contents and biomechanical properties as the native menisci in the sham operation group Chen et al (2019) Porcine meniscal fibrochondrocytes Agorose, methacrylated gelatin (GelMA), methacrylated hyaluronic acid (MeHA) and GelMA-MeHA blend hydrogels Fibrochondrocytes (passage 2) were reconstituted in the polymer solutions prior to photocuring and then cultured in fibrochondrogenic medium Hydrogels have a higher potential for meniscal regeneration than the 3D printed PCL, and fibrochondrocytes could be directed to proliferate or produce cartilaginous or fibrocartilaginous ECM.…”
Section: Natural Biomaterial-derived Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high diversity of chemical structures and properties of these plant polysaccharides opens the possibility for their application in several fields, including in the food area (e.g., as gelling agents) [ 97 ], in the biomedical field (e.g., in drug delivery systems) [ 98 ], and, more recently, in tissue engineering [ 99 ]. The interest in using some of these plant-derived polysaccharides in the formulation of bioinks for 3D bioprinting applications has also grown considerably in the later years, as summed up in Table 2 , with several works using cellulose and nanocelluloses [ 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 ] and pectin [ 119 , 120 ].…”
Section: Polysaccharide-based Hydrogel Bioinksmentioning
confidence: 99%
“…CELLINK Bioink from Cellink [ 132 ]; throughout the years, not much evolution and creativity has been observed regarding the use of NFC as a bioink component. Most recent studies still describe its combination with alginate for bioprinting of different cell lines, namely human cartilage [ 115 , 116 ], human dermis [ 117 ], bone [ 102 , 118 ], and skeletal muscle [ 103 ]. Additionally, nanocelluloses are still mainly used as reinforcing components for hydrogel bioinks due to their excellent mechanical properties.…”
Section: Polysaccharide-based Hydrogel Bioinksmentioning
confidence: 99%